"Jesteście najlepszym, co mam". Oriana Fallaci jako córka = "You are the best I have". Oriana Fallaci as a daughter - Tichoniuk-Wawrowicz, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Over time, Oriana Fallaci increasingly referred to her books as "paper children". This anthropomorphism gradually grew in strength, becoming a subliminal explanation of her choices. Not having tasted parenting herself, Fallaci could only watch it from the outside, trying to legitimize its full understanding through a creative act. She talked about her own parents with delight: she presented them as exceptional people and herself as a dedicated daughter.
Keywords: Fallaci, Oriana (1929-2006); daughterhood; autobiographism; autocreation; parent-child relationship; autobiografia; autokreacja; stosunki rodzic-dziecko